2022
DOI: 10.1002/jcop.22881
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring social‐emotional learning, school climate, and social network analysis

Abstract: There is currently limited research on student peer leadership in the social‐emotional literature. This paper used exploratory methods of social network analysis to understand the structure of school peer relationships, peer leadership, and school climate. Self‐report measures of perceptions of peer leadership and climate were given to students during the 2016–2017 school year. Data collected from a peer leadership survey were used to calculate closeness and indegree centrality values. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…One of the overarching themes found was the lack of existing research that counselors could use to adapt or mold existing therapy practices to best suite their neurodivergent clients. Mitran also shared ideas such as using social emotional learning, universal design learning, and social learning theories to support this population of clients Social emotional learning is a theory which supports the use of including the social and emotional surroundings a client interacts with on a day-to-day basis in their treatment (Xu, MacDonnell, Wang & Elias, 2023). Social learning theory is common in substance use counseling and it encourages a clinician to guide a client in recognizing how their substance use…”
Section: Dear Editormentioning
confidence: 99%
“…One of the overarching themes found was the lack of existing research that counselors could use to adapt or mold existing therapy practices to best suite their neurodivergent clients. Mitran also shared ideas such as using social emotional learning, universal design learning, and social learning theories to support this population of clients Social emotional learning is a theory which supports the use of including the social and emotional surroundings a client interacts with on a day-to-day basis in their treatment (Xu, MacDonnell, Wang & Elias, 2023). Social learning theory is common in substance use counseling and it encourages a clinician to guide a client in recognizing how their substance use…”
Section: Dear Editormentioning
confidence: 99%
“…However, there is also evidence that suggests that the effectiveness of school-based intervention programs, including SEL, may be affected by individual characteristics of students and the characteristics of schools ( Hughes et al 2005 ). For example, prior research has indicated that students who identify as female tend to report higher climate scores for their schools than students who identify as male ( Keppens and Spruyt 2019 ; Koth et al 2008 ; White et al 2014 ; Xu et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%